From Thought to Speech: The Psycholinguistics Process of Foreign Language Sentence Production - Hawa Alfina Salsabil; Fara Audina Lubis; Sahfitri Ahwani; Yani Lubis (International Journal Multidisciplinary Science, 2026)
This study explores the psycholinguistic processes underlying foreign language sentence production, focusing on how EFL learners transform thoughts into spoken language. Using a qualitative phenomenological approach, twelve English Education students from a university in Medan participated in speaking tasks, think-aloud protocols, and semi-structured interviews. Thematic analysis revealed three major processes: cognitive planning and conceptualization, lexical retrieval and formulation, and monitoring and repair in speech. Learners experienced high cognitive load due to limited working memory, leading to pauses, reformulations, and simplifications during speaking. To cope, they employed compensatory strategies such as segmentation, paraphrasing, and self-correction to maintain communication flow. The findings indicate that fluency and accuracy depend on the balance between linguistic knowledge and cognitive capacity. This study contributes to psycholinguistic understanding by illustrating how thought, language, and cognition interact in real-time sentence production and provides pedagogical implications for promoting automaticity and cognitive awareness in EFL speaking instruction.